Database Management (DBM) in a Changing Environment - Olowu, ThankGod C. (Richtmann Publishing, 2011)
The views of this paper expressed the management of the database system that enhances the importance usage ofcomputer network to ascertain the task. This describes a serious research to enabling profound solutions on the solvedkeywords. Universal Database is a relational database management system that supports a variety of client and server platformsand communications protocols. Database management is made up of several administration tools such as the control center andthe command center, which simplify the task of managing your environments and data. The basic elements used by universaldatabase objects, data integrity, system catalog tables, directories, storage objects, recovery objects, and configuration files.Database provides several system management facilities to help manage very large data-base and large networks. Thosefacilities includes being able to perform many administration management tasks while users are still connected to the database,allowing client code to be shared to simplify configuration, and a governor to assist you define how applications behave.Database management program files are physically stored in one location on a particular machine, and created instant pointback to the location, and can have several related database located within a single instance.